Moderate iron deficiency and high dietary iron intake differentially alter hepatic lipid metabolism and adipose tissue lipid handling in mice - Wu, Shangjie; Li, Pengwei; Liu, Qian; Zhang, Keying; Ding, Xuemei; Wang, Jianping; Zeng, Qiufeng; Liu, Yan; Xuan, Yue; Li, Shanshan; Mu, Yadong; Bai, Shiping (Frontiers in Nutrition, 2026)
BackgroundIron (Fe) is an essential micronutrient, yet both its deficiency and overload have been associated with disruptions in lipid metabolism. This study investigated the effects of moderate iron deficiency and high dietary iron on lipid metabolic pathways in mice.MethodsFive-week male C57BL/6J mice were fed for 16 weeks on one of three diets: a basal iron-deficient diet without iron supplementation (FeD, 19.26 mg/kg Fe), and the same basal diet supplemented with either 200 mg Fe/kg (iron-adequate control, Control) or 1,200 mg Fe/kg (high-iron, FeH). Growth performance, iron status, serum lipids, tissue iron deposition, hepatic fatty acid composition, and expression of key genes and enzymes involved in lipid metabolism were analyzed.ResultsThe FeD group exhibited increased body weight and feed intake, and reduced systemic iron parameters. Molecular analysis revealed a distinct pattern of lipid metabolic disruption in FeD, characterized by the upregulation of certain hepatic lipogenic transcripts (ACLY, SREBP1c, PPARγ) but without a concomitant increase in functional lipogenic output or hepatic triglycerides. Notably, the elevation in SCD1 protein occurred alongside a decreased hepatic C18:1 n-9/C18:0 ratio in the FeD group. In adipose tissue, FeD specifically enhanced lipolysis gene expression (ATGL, HSL, FABP4), indicating elevated lipid mobilization. In contrast, FeH mice developed hyperlipidemia and hepatic iron overload, which was driven by direct activation of the hepatic SREBP1c pathway and its lipogenic targets (ACC, FAS, SCD1). Hamp expression was significantly upregulated in the FeH group compared to both the control and FeD groups (p < 0.05). Although both diets altered hepatic fatty acid composition, they operated through fundamentally distinct mechanisms.ConclusionsThese findings demonstrate that moderate iron deficiency and high iron intake disrupt hepatic lipid metabolism via different pathways: FeD primarily through systemic adaptations leading to post-translational constraints on iron-dependent enzymes, whereas FeH acts through direct transcriptional activation of hepatic de novo lipogenesis, potentially involving hepcidin-mediated cross-talk. The study underscores the critical importance of iron homeostasis in preventing dyslipidemia and hepatic steatosis and provides mechanistic insights that could inform dietary recommendations for populations at risk of metabolic disorders.